2022
DOI: 10.1111/ina.12976
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the factors that influence exposure to SARS‐CoV‐2 on a subway train carriage

Abstract: We propose the Transmission of Virus in Carriages (TVC) model, a computational model which simulates the potential exposure to SARS‐CoV‐2 for passengers traveling in a subway rail system train. This model considers exposure through three different routes: fomites via contact with contaminated surfaces; close‐range exposure, which accounts for aerosol and droplet transmission within 2 m of the infectious source; and airborne exposure via small aerosols which does not rely on being within 2 m distance from the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 43 publications
(108 reference statements)
0
19
0
Order By: Relevance
“…The decay in the viability of the virus in droplets was not included. While some of these effects could be included in a CFD model, it would be more effective to include others in a higher‐level model, such as a quantitative microbiological risk assessment model 41 …”
Section: Resultsmentioning
confidence: 99%
“…The decay in the viability of the virus in droplets was not included. While some of these effects could be included in a CFD model, it would be more effective to include others in a higher‐level model, such as a quantitative microbiological risk assessment model 41 …”
Section: Resultsmentioning
confidence: 99%
“…In addition, the link between COVID-19 transmission and public transportation has been found to be mixed ( Gartland et al, 2022 ). While using public transportation, measures such as the wearing of masks, physical distancing, air conditioning, and filtering on public transit may contain the spread of COVID-19 effectively (Kriegel, 2022; Miller et al, 2022 ; Muathesis, 2022; Yang et al, 2022 ). Quarantine measures, such as suspension of operations or restrictions to prevent the spread of infectious diseases, may cause unexpectedly high socioeconomic costs, such as increases in mental health conditions and the deepening of socioeconomic inequality ( Fink et al, 2022 ; Koch and Park, 2022 ; Thunström et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…They also argued that the routes and main factors of public transit in diffusing COVID-19 were still unclear during the early experiences of the pandemic. Some studies have found that such measures such as mask wearing, physical distancing, air conditioning, and filtering on public transit have a significant impact on reducing exposure to COVID-19 transmission ( Kriegel et al, 2021 ; Matheis et al, 2022 ; Miller et al, 2022 ; Yang et al, 2022 ). Musselwhite et al (2020) argues that restrictions on the operation of overcrowded public transit due to the higher possibility of individual transmission of COVID-19 needs to be well thought because the exposure in households can be higher.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the role that public transport plays in the transmission of infectious diseases is not well-understood, although there is some epidemiological evidence that it could contribute to the transmission of influenza-like illness ( 7 , 8 ), and high-touch surfaces on public transport vehicles are known to be contaminated with bacteria ( 9 ) and can be contaminated with SARS-CoV-2 RNA ( 10 , 11 ). A recent modeling study that compared the relative contributions of close-range exposure to SARS-CoV-2 (via droplets or aerosols), airborne exposure (via small aerosols without having to be within 2 meters of the infectious source), and exposure via contaminated fomites in a subway carriage concluded that all three routes of transmission are relevant in this setting ( 12 ).…”
Section: Introductionmentioning
confidence: 99%